Gambaran kemanfaatan fasilitas internet untuk menunjang pembelajaran pada mahasiswa Program Sarjana Keperawatan Universitas Jenderal Soedirman - Kamaluddin, Ridlwan; Asrin (Jurnal Keperawatan Soedirman, 2008)
Student of Nursing Program, Faculty of Medicine and Health Science Soedirman University use internet facility as source of information, communication and entertainment. Nursing student used facility internet both for made available in faculty and also outside faculty. Internet Library of Nursing Program has amounting to 20 computers, all of computers use the processor pentium 4. This facility subscribe to the journal of proquest and ebsco by providing about 600 journals. According to the survey research, the librarian said that there are approximately 40 – 60 students per day using internet. However it cannot be seen yet how its effectiveness is.The aim of this study is to describe the benefit of usage of internet facility to support learning teaching process. This Research is explorative descriptive qualitative. Subject of this research is student nurses. Collecting data use in depth interview, focus group discussion and documentation study toward visit book of internet facility in Nursing Program Soedirman University Documentation study toward visit book of internet facility in Nursing Program library of Soedirman University on 1 May until 28 June 2007 show that almost the visitor in internet facility are nursing students. Web browser and e-mail are internet facility that are often accessed. Yahoo and Google is the most popular website around nursing student. Internet has role in accomplishment of learning tasks. Nevertheless internet less influence students to do the access faster and to collect task if they get tasks. The usage of internet its felt efficient on time because in looking information is getting faster. But less efficient on cost, because it must spent a lot cost. Generally nursing students feel satisfy to use the internet to look for the information because a lot of information can be got there. Most of students do access internet minim once a week. Although in the beginning they get difficulty to use the internet, they become easier than, because they often access internet. Several difficulty access internet are: lack of knowledge of website address, keyword, language, items and science of internet. Ability that is owned to access internet is still less. By and then student nurses experience increasing